NEWS FRAMING ANALYSIS: The Decreased of Ganjar Pranowo's Electability in the 2024 Election Contestation - Muhammad Zahrul Asyhary; Sri Hastjarjo; Andre Noevi Rahmanto; Rengga Mahendra (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
Elections serve as a means for Indonesian citizens to participate in shaping the direction of the country's politics and creating a government that represents the aspirations of the people. Mass media, including online news sites, play a crucial role in shaping public perception and opinions on political issues, including the electability of presidential candidate Ganjar Pranowo. This research aims to analyze the perspectives of online media outlets detik.com, kompas.com, and tempo.co in framing the news about the decreased in Ganjar Pranowo's electability after the Israel team's rejection statement, and Ganjar Pranowo being highlighted as one of the figures behind Indonesia's cancellation as the host of the FIFA U-20 World Cup. This research is of a qualitative nature, utilizing the framing analysis method. Furthermore, the framing analysis is conducted using the Zhongdang Pan and Gerald M Kosicki analysis model. The subjects of this study are news samples related to the decreased in Ganjar Pranowo's electability published on detik.com, kompas.com, and tempo.co online media on May 19, 2023. The results of this research indicate that the framing of online media detik.com and kompas.com related to the decreased in Ganjar Pranowo's electability tends to be positive. In contrast, the framing of tempo.co online media tends to be negative in reporting the decreased in Ganjar Pranowo's electability. This research is expected to provide a deeper understanding of how positive or negative media framing can influence public sympathy. Additionally, this study can raise awareness among the public about the potential influence of mass media on the political process and understanding how to consume news wisely and critically.